Hepatoblastoma: From Molecular Mechanisms to Therapeutic Strategies - Ling Fan; Jintong Na; Tieliu Shi; Yuan Liao (Current Oncology)
Hepatoblastoma (HB) is the most common malignant liver tumor in children under five years of age. Although globally rare, it accounts for a large proportion of liver cancer in children and has poor survival rates in high-risk and metastatic cases. This review discusses the molecular mechanisms, diagnostic methods, and therapeutic strategies of HB. Mutations in the CTNNB1 gene and the activation of the Wnt/β-catenin pathway are essential genetic factors. Furthermore, genetic syndromes like Beckwith–Wiedemann syndrome (BWS) and Familial Adenomatous Polyposis (FAP) considerably heighten the risk of associated conditions. Additionally, epigenetic mechanisms, such as DNA methylation and the influence of non-coding RNAs (ncRNAs), are pivotal drivers of tumor development. Diagnostics include serum biomarkers, immunohistochemistry (IHC), and imaging techniques. Standard treatments are chemotherapy, surgical resection, and liver transplantation (LT). Emerging therapies like immunotherapy and targeted treatments offer hope against chemotherapy resistance. Future research will prioritize personalized medicine, novel biomarkers, and molecular-targeted therapies to improve survival outcomes.